LOW WATER TEMPERATURE AND ITS EFFECTS ON STRESS RESPONSE OF GREY MULLETS Mugil cephalus ACCLIMATED IN FRESHWATER - Vitas Atmadi Prakoso; Jojo Subagja; Young Jin Chang (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2015)
Grey mullet (Mugil cephalus) can adapt to saline and freshwater. Although belonged to euryhaline species, but information regarding their stress response on low temperature. Environmental disturbance such as low water temperature may effect their physiological condition. These information can be useful for aquaculture development of this species in freshwater. Therefore, the purpose of study was to investigate the effects of low water temperature on the stress response of grey mullets Mugil cephalus acclimated in freshwater. The blood samples of experimental fish (TL: 28.2±1.1 cm, BW: 198.6±25.9 g) were collected during winter season when the water temperature of controlled rearing system was stable at 25°C and uncontrolled rearing system slowly dropped until 12°C. Their stress response on both rearing systems was observed. The results showed that low temperature affected to lower the behavior activity and increase the stress response of grey mullets. The breath frequency of grey mullet regarding their opercular movement at 12°C was 74-97 breath/min., while at 25°C it was 95-114 breath/min. Hematocrit (Ht) and hemoglobin (Hb) were shown higher values of 43.5% and 9.5 g/dL, respectively at 25°C than 12°C (28.0% and 7.1 g/dL, respectively). The tendencies of cortisol and glucose level increased with the lowering temperature, showing higher value of 264.8 ng/mL and 35.5 mg/dL in 12°C than 5.5 ng/mL and 32.7 mg/dL in 25°C. The chemical properties of blood in grey mullets showed same tendency comparing between 12°C and 25°C, there was no significant different between each temperature, except for chloride (P<0.05). Chloride value was higher at 25°C, while other blood components such as osmolality, sodium, potassium, and magnesium were showing no significant differences. However, the results showed lower values at 12°C in every blood components, except for chloride. In conclusion, lowering water temperature to 12°C had impact as stressor to the behavior and stress response of grey mullets acclimated in freshwater.